TIME OPTIMIZATION USING CPM, PERT AND PDM METHODS IN THE SOCIAL AND DEPARTMENT OF KELAUTAN BUILDING DEVELOPMENT PROJECT GRESIK DISTRICT - Ardabil Maulana; Fredy Kurniawan (NAROTAMA UNIVERSITY, Indonesia)
Planning a project there are many important things that affect the success and smoothness, one of which planning time implementation of the right and efficient work. The way to overcome the problem is by using several methods such as CPM (Critical Path Method), PERT (Project Evaluation and Review Teqnique), PDM (Precedence Diagram Method). From the calculation result show that the duration of project completion using CPM method is 57 weeks, project completion duration using PERT method is 78 + 7.5 weeks with the probability of achieving project completion time target is 99.87% and project completion duration using PDM method is 30 weeks. So the method that best suits the Social Service Development Project and the Office of Marine Gresik Regency is the PDM method because the PDM method is capable of producing shorter project completion periods than the CPM and PERT methods of 30 weeks.